Effective frequency of displaying the communication message to consumers of beer brand in digital media - Semenenko, Katerina; Kapinus, Larisa; Boyko, Irina; Kucherenko, Volodymyr; Skryhun, Natalya (My University, 2022)
The research is devoted to the determining of effective display frequency of advertised communication messages to consumers in representative samples of the enterprise of brewing industry to optimize the media budget. The research is based on the scientific researches of scientists on the development of beer market and digital economy, theories of advertisement message frequency, marketing research of brewing enterprises and their brands to determine the minimum range of effectiveness of advertised messages to beer consumers. The frequency of displaying the communication message determines not only the effectiveness of appeals to the consumer, but also spending on media budget, however, currently there is no single point of view to this problem in scientific researches. Both as unsufficient amount of appeals and an excessive frequency lead to insufficient budget using. Effective frequency of the message influences not only on consumer’s purchasing behavior and indicators of brand’s health but also allows to optimize media budget. Certainly, mostly mediaplanners use effective frequency strategy «three plus». In order to determine the frequency of communication with consumers for instruments of online-advancement of beer the modified Matrix of Ostrow is given. The blocks of factors of influence on beer promotion on the consumer market are improved, they are «Market factors», «Factors of quality of advertisement message», «General mediafactors». «Online mediafactors» block is added, where such indexes as description of placement the resources, use of social media, use of videoformats, use of non-standard displays and formats, coverage of mediachannel, type of placement, accordance to general content of campaign are considered. Adaptation of the improved matrix took place on the example of the most beer brands of the market, for this reason the effective frequency of repeatition of communication message and comparing to actual is carried out, that allowed to group brands into 4 groups from position of strategy of further charges to placement of advertised messages in the Internet. Дослідження спрямоване на визначення ефективної частоти показу рекламних повідомлень споживачам у репрезентативній вибірці підприємств пивоварної галузі для оптимізації медійного бюджету. Дослідження ґрунтується на результатах праць науковців з питань розвитку ринку пива та цифрової економіки, теорій частоти рекламних повідомлень, маркетингових досліджень найбільших пивоварних компаній та їх брендів для визначення мінімального порогу ефективної частоти рекламних звернень до споживачів пива. Частота показу комунікаційного повідомлення визначає не лише ефективність звернень до споживача, але й витрати на медійний бюджет, проте, наразі відсутня єдина точка зору на цю проблему у наукових публікаціях. Як недостатня кількість звернень, так і надмірна частота призводять до неефективного використання бюджету. Ефективна частота повідомлення впливає не тільки на купівельну поведінку споживача та показники здоров’я бренду, а й дозволяє оптимізувати медійний бюджет. Визначено, що найчастіше в медіаплануванні використовують ефективну частотну стратегію «три плюс». З метою визначення ефективної частоти комунікацій зі споживачами для інструментів онлайн-просування пива запропоновано модифіковану матрицю Остроу. Удосконалено блоки факторів, які впливають на просування пива на споживчий ринок: «Ринкові чинники», «Чинники якості рекламного повідомлення», «Загальні медіачинники». Додано блок «Онлайн-медіачинники», куди увійшли такі показники, як характеристика ресурсів розміщення, використання соціальних медіа, використання відеоформатів, використання нестандартних проявів і форматів, охоплення медіаканалу, тип розміщення, відповідність загальному контенту кампанії. Адаптація удосконаленої матриці відбулась на прикладі найбільших пивних брендів ринку, для яких було визначено ефективну частоту повторень комунікаційного повідомлення та здійснено порівняння із фактичною, що дозволило згрупувати бренди у 4 групи з позиції стратегії подальших витрат на розміщення рекламних повідомлень в мережі Інтернет.
Keywords: кафедра маркетингу; frequency; communication; coverage; digital marketing; online-advertisement; частота; комунікація; охоплення; цифровий маркетинг; онлайн-реклама